JKSE AND TRADING ACTIVITIES BEFORE AFTER COVID-19 OUTBREAK - Dewi, Catur Kumala (RJABM (Research Journal of Accounting and Business Management), 2020)
The Covid-19 outbreak gave a negative implication not only on the Indonesian stock exchange but throughout the world until WHO declared Covid-19 a pandemic. Stock market movements are formed by stock market participants, including issuers, brokers and investors. IHSG continues to fluctuate sharply and tends to decrease in the beginning of January 2020 to April 2020. Different things happen for trading volumes that have increased.  Trading volume is a combination of sell and buy during the trading session. Before and after Covid-19, IHSG gives an illustration that trading volume is increasingly fluctuating sharply with an upward trend above trading volume before Covid-19. Pandemic provides an overview of IHSG volatility and trading volumes that experience sharp fluctuations with a downward trend. Therefore, reserves are better if diversification is carried out in real assets other than financial assets.